2016
DOI: 10.1002/sdtp.10713
|View full text |Cite
|
Sign up to set email alerts
|

37-4L:Late-News Paper: Development of a 27-in. 8K x 4K Liquid-Crystal Display Utilizing an InGaZnO TFT Backplane

Abstract: We have successfully developed 27inch 8K4K Liquid Crystal display by utilizing BCE IGZO (Back Channel Etched InGaZnO) transistor. Its pixel density is 326ppi like smartphone, but the screen size is 27inch, middle class desktop monitor size. And its LCD panel supports 120Hz driving. BCE IGZO-TFT realizes low resistance wiring material because of its low process temperature. Above reason, we can enlarge the screen size to desktop monitor class, remaining smartphone class fine resolution. Also this system conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…As the size and resolution of the LCD increase, the resistance and capacitance (RC) loads of the display panel also increase, thus making it difficult to charge the subpixel and degrading the image quality of the display. Several thin‐film transistors (TFTs) have been researched for subpixel charging in the display panel, which is highly dependent on the characteristics of the TFTs used in the panel . Amorphous silicon TFTs and low‐temperature polysilicon TFTs have been widely used to date but have suffered from low mobility and non‐uniform characteristics, respectively .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the size and resolution of the LCD increase, the resistance and capacitance (RC) loads of the display panel also increase, thus making it difficult to charge the subpixel and degrading the image quality of the display. Several thin‐film transistors (TFTs) have been researched for subpixel charging in the display panel, which is highly dependent on the characteristics of the TFTs used in the panel . Amorphous silicon TFTs and low‐temperature polysilicon TFTs have been widely used to date but have suffered from low mobility and non‐uniform characteristics, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…Several thin‐film transistors (TFTs) have been researched for subpixel charging in the display panel, which is highly dependent on the characteristics of the TFTs used in the panel . Amorphous silicon TFTs and low‐temperature polysilicon TFTs have been widely used to date but have suffered from low mobility and non‐uniform characteristics, respectively . In recent years, indium gallium zinc oxide TFTs with relatively high mobility and uniform characteristics were developed for the backplane of displays in order to solve the subpixel charging issues in large‐sized and high‐resolution LCDs …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent times, ultra‐high‐definition (UHD: 3840 × 2160) liquid crystal display televisions (LCD TVs) with high image quality have been sold in large numbers worldwide. Moreover, 8 k × 4 k LCD TVs have been demonstrated by some display companies . Several studies have reported on the technical aspects of realization of 8 k × 4 k LCD TVs in recent years .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 8 k × 4 k LCD TVs have been demonstrated by some display companies. [1][2][3][4][5][6] Several studies have reported on the technical aspects of realization of 8 k × 4 k LCD TVs in recent years. [7][8][9][10] One of the most important technical issues pertaining to these LCD TVs, as reported in such studies, is the line delay that is also called a resistor-capacitor (RC) delay because of the heavy load on electrical lines.…”
Section: Introductionmentioning
confidence: 99%